Die angewandte Geländeklimatologie - ein aktuelles Arbeitsgebiet der physischen Geographie - Wanner, Heinz (ERDKUNDE, 1986)
In the first part of this paper the position of applied topoclimatology within climatology and geography is discussed. In the second part the objectives, the working areas and the methods are described. It is shown that geographically aligned, applied topoclimatology employs typical methods or working techniques which are specifically adapted to spatial analysis: synoptic climatology, spatial (and temporal) representation of climatological variables or processes (using digital terrain models and computer cartography), combination of conventional with remote sensed data, statistical and (rarely) numerical modelling. The following are typical working areas of applied topoclimatology: (i) the search for suitable area for agriculture or tourism; (ii) the preparation of data which help to minimize expenditure of energy in general or to optimize the use of passive energy; (iii) the development of fundamentals which contribute to reducing negative effects in urban or industrial planning (air pollution, heat stress, gusts of wind, etc.). Finally, the application of the working techniques mentioned above is demonstrated by an example taken from applied agrotopoclimatology: The climatological potential related to vine growing in the northern Swiss Jura is evaluated using different data types (15 fixed meteorological stations and an instrumented, mobile measuring car).